2013
DOI: 10.1038/nsmb.2511
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the MutLα C-terminal domain reveals how Mlh1 contributes to Pms1 endonuclease site

Abstract: Mismatch-repair factors have a prominent role in surveying eukaryotic DNA-replication fidelity and in ensuring correct meiotic recombination. These functions depend on MutL-homolog heterodimers with Mlh1. In humans, MLH1 mutations underlie half of hereditary nonpolyposis colorectal cancers (HNPCCs). Here we report crystal structures of the MutLα (Mlh1-Pms1 heterodimer) C-terminal domain (CTD) from Saccharomyces cerevisiae, alone and in complex with fragments derived from Mlh1 partners. These structures reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
156
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(165 citation statements)
references
References 59 publications
9
156
0
Order By: Relevance
“…Although this motif is similar to the canonical PCNA-interacting peptide motif (16), the recent structure of the yMutLα CTD (Fig. 3) has shown that this heptapeptide element is buried and unlikely to be involved in yPCNA interaction in the absence of a substantial conformational change (9). A second potential PCNA-interaction motif within the PMS2 CTD has been suggested by studies of the interaction of B. subtilis MutL with the β-clamp, an interaction that depends on a QEMIVP motif within the CTD of the MutL homodimer (14).…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Although this motif is similar to the canonical PCNA-interacting peptide motif (16), the recent structure of the yMutLα CTD (Fig. 3) has shown that this heptapeptide element is buried and unlikely to be involved in yPCNA interaction in the absence of a substantial conformational change (9). A second potential PCNA-interaction motif within the PMS2 CTD has been suggested by studies of the interaction of B. subtilis MutL with the β-clamp, an interaction that depends on a QEMIVP motif within the CTD of the MutL homodimer (14).…”
Section: +mentioning
confidence: 99%
“…The MutLα endonuclease center resides within the heterodimeric C-terminal domain (CTD) that is composed of the C-terminal domains of MLH1 and PMS2 (PMS1 in yeast) (9), and endonuclease function depends on the integrity of a DQHA(X) 2 E(X) 4 E metal-binding active-site motif located within the PMS2/yPMS1 CTD (5,6). The DQHA(X) 2 E(X) 4 E endonuclease motif is also conserved in MutL proteins from bacteria that do not rely on d(GATC) methylation for strand direction of MMR, with Bacillus subtilis MutL the most extensively studied protein of this class.…”
mentioning
confidence: 99%
“…Mutations in a DQHAX 2 EX 4 E metal binding motif present in both human Pms2 and yeast Pms1 disrupt both MLH endonuclease activity and MMR (5)(6)(7). Recently, two groups reported the crystal structures of the endonuclease domain of MLH proteins (8,9). For Bacillus subtilis MutL, the endonuclease domain consisted of dimerization and regulatory subdomains connected by a helical lever spanning the conserved endonuclease motif.…”
Section: Dna Mismatch Repair (Mmr)mentioning
confidence: 99%
“…Unlike in E. coli, there are no MutH homologues in eukaryotes. However, MutL␣ has been shown to possess a cryptic endonuclease activity, which is dependent on the integrity of the DQHAX 2 EX 4 E motif within human PMS2 or yeast Pms1 (12)(13)(14)(15). In contrast to MutS␣ and MutS␤, MutL␣ has very low affinity for DNA and shows no preference for mismatches (16,17).…”
mentioning
confidence: 96%